Premature Mortality among People with Severe Mental Illness – New Evidence from Linked Primary Care Data. (2018) - Lee, Sze Chim; John, Ann; McGregor, Joanna; Jones, Ian; Walters, James; Owen, Michael; O'Donovan, Michael; Banos, Marcos del Pozo; Berridge, Damon; Lloyd, Keith
No abstract available